2004
DOI: 10.1523/jneurosci.2981-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Regeneration and Lack of Astrocytic Gliosis in EphA4-Deficient Mice

Abstract: Spinal cord injury usually results in permanent paralysis because of lack of regrowth of damaged neurons. Here we demonstrate that adult mice lacking EphA4 (Ϫ/Ϫ), a molecule essential for correct guidance of spinal cord axons during development, exhibit axonal regeneration and functional recovery after spinal cord hemisection. Anterograde and retrograde tracing showed that axons from multiple pathways, including corticospinal and rubrospinal tracts, crossed the lesion site. EphA4Ϫ/Ϫ mice recovered stride lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
274
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(291 citation statements)
references
References 59 publications
11
274
4
1
Order By: Relevance
“…Members of this family are up-regulated following CNS injury (18,19). EphA4 has been implicated in the response to injury both as an astrocyte and as a neuronally expressed protein, but its functional role in recovery from neuronal injury is not clear (20)(21)(22)(23). Macrophage EphB3 has also been implicated in adult axon regeneration (24).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
“…Members of this family are up-regulated following CNS injury (18,19). EphA4 has been implicated in the response to injury both as an astrocyte and as a neuronally expressed protein, but its functional role in recovery from neuronal injury is not clear (20)(21)(22)(23). Macrophage EphB3 has also been implicated in adult axon regeneration (24).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
“…Many studies have modulated the gliotic scarring response by enzymatic digestion, antibody blocking, or clonal deletion of specific glial scar molecules to promote axon regeneration and functional SCI recovery (Bradbury et al, 2002;Goldshmit et al, 2004;Shearer et al, 2003). Although these biochemical approaches show promise, the therapeutic effects are relatively limited because of the multiple molecule candidates and complicated scar microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vitro neurite outgrowth studies demonstrated that a significant part of myelin inhibition is mediated by Ephrin-B3, which remarkably equals to the inhibitory activity of Nogo, MAG, and OMgp combined -at least for the postnatal cortical neurons tested (Benson et al, 2005). Interestingly, an independent group reported robust axonal regeneration and improved functional recovery in mice lacking EphA4, the receptor for Ephrin-B3 during CST development (Goldshmit et al, 2004). Furthermore, several potential mechanisms for improved axon regeneration and functional recovery were suggested, including a loss of EphA4-mediated axon growth inhibition, reduced astrogliosis and altered vascular remodeling (Goldshmit et al, 2004;Goldshmit et al, 2006).…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%
“…Interestingly, an independent group reported robust axonal regeneration and improved functional recovery in mice lacking EphA4, the receptor for Ephrin-B3 during CST development (Goldshmit et al, 2004). Furthermore, several potential mechanisms for improved axon regeneration and functional recovery were suggested, including a loss of EphA4-mediated axon growth inhibition, reduced astrogliosis and altered vascular remodeling (Goldshmit et al, 2004;Goldshmit et al, 2006). Taken together, these studies illustrated a new role for developmentally critical axon guidance molecules in axon growth inhibition and other important aspects of CNS injury and repair.…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%